Checking Mehr housing development policies in the framework of infill development from View residents Mehr housing of Mahabad city - yousouf Bahrami; ghaderymotlagh iraj; behroz oftadeh; sid ali hosieni (تحقیقات کاربردی علوم جغرافیایی)
The present study aimed to assess the conformity of Mehr housing projects by Infill development pattern to answer this question: What is the relationship between Mehr housing project in the city of Mahabad with Infill development and with its spatial conditions of the city. The research method in present study in terms of nature is "descriptive – survey" and in terms of purpose "applied" and in terms of collecting data is " field." Statistical society is the whole members of Mahabad Mehr housing that were determined 361 persons as sample by Cochran formula. To data analysis was used the methods of descriptive statistics (frequency, percentage, mean, standard deviation) and inferential statistics (one-sample t-test). The results show that Mehr housing policies in the city of Mahabad not comply with its physical conditions. T-test results in this study showed that Infill development due to the use of the maximum of capacity available space of city, Can be considered as a suitable model and as the basis to guide Mehr housing policy in the city of Mahabad. The results of T-test about the physical factors (t-=1/48; p-value<0/05), socio-cultural factors (t=24/35; p-value≥ 0/05), economic factors (t=13/27; p-value≥0/05) and environmental factors (t=27/29; p-value≥0/05) shows that Mehr housing policies in the city of Mahabad comply with socio-cultural factors, economic factors and environmental factors but not comply with its physical conditions.